Penerapan Metode Karya Wisata untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik pada Pembelajaran IPA Kelas V SD N Krenceng I - Andriana, Encep; Muhyidin, Asep; Pahamzah, John; Afrizal, Muhamad (Jurnal Ilmiah Wahana Pendidikan, 2024)
This field trip method is a method used in presentation by bringing students to study the material outside the classroom (outdoor). Field trip activities can also utilize the surrounding environment as a learning resource, and can foster responses to students' creative stimulation, the information obtained by students will also become broader, more current and concrete, and students can also process or search for information themselves. . Research using a descriptive qualitative approach or what is usually referred to as qualitative research. The subjects in this research were class V teachers at SDN Krenceng I. Data collection in this descriptive qualitative research used observation, interviews and documentation methods. From the results of this research, it has been proven that SDN Krenceng I has implemented the field trip method in its learning by visiting educational places such as the Cikerai livestock villa where students are taught to learn outside the classroom with various things that students must pay attention to or observe.